Virtual reality for education on infection prevention and control: the impact on medical students’ knowledge, attitudes and practices - Bente Schippers; Olga Coenen; Franka Luk; Mark Graner; Frans van Hoek; Nike Stikkelbroeck; Machteld Dronkers; Edmée Bowles; Alma Tostmann (Antimicrobial Resistance and Infection Control)
Abstract Background This study aims to analyse the impact of a newly developed infection prevention and control (IPC) Virtual Reality (VR)-module on medical students’ IPC knowledge, attitudes and practices. Additionally, the impact of the module on students’ and healthcare professionals’ (HCPs) confidence regarding IPC decision-making and their insight into consequences of IPC decisions were analysed. Methods The IPC VR-module was developed using a cyclical design process consisting of a prototype, first and final version. Knowledge, attitudes and practices (KAP) regarding IPC were compared between two groups of medical students. The VR-module was added to the IPC program for the VR group. After completion of the program, students of both groups were asked to complete an online questionnaire. Scores were summated for each subscale of the KAP, a Mann-Whitney U test was performed to compare scores between groups. Student and HCP responses to VR-specific questions were dichotomized and a chi-square test was used to compare responses to different versions of the module. Results Students who completed the VR-module (n = 34) scored higher on IPC knowledge questions (score 8 / 10), than those who followed the regular program (n = 58; score 7/10; p = 0.003). For the final version, the added value of the VR-module in the program was recognized by 95% of students and 90% of HCPs. Students and HCPs who completed the final version of the VR-module agreed more often with learning objectives of the VR-module than those who completed the first version. 100% vs. 80% for the statement on insight into consequences of choices (p < 0.001) and 89% vs. 73% for the statement on confidence taking IPC decisions (p < 0.001). Conclusions The innovative IPC VR-module positively impacted students IPC knowledge and was highly appreciated by students and HCPs. VR-specific learning objectives were achieved, especially for the final version of the VR-module, demonstrating the importance of a cyclical design process.